(untitled) (Bangladesh Journal of Medical Science, 2023)
Objectives: The correct determination of the vertebral level is important in anesthesia management and the prevention of possible risks. It has been shown that estimation of L4/5 intervertebral lumbar level based on Tuffier’s line determined by palpation (palpated L4/5) is often inaccurate. In this study, it was aimed to investigate how Tuffier’s line changes in the lateral decubitus position due to pregnancy. Material and Methods: The patients were divided into two groups in this prospective cohort study. The pregnant patients were assigned to Group P (n = 75) while the non-pregnant patients were assigned to Group NP (n = 60). Lumbar ultrasound was conducted in both groups in the left lateral decubitus position to verify the vertebral level determined by Tuffier’s line that was detected by palpation. Demographic data, determination time of Tuffier’s line, ultrasound, and the detected vertebral levels were recorded in both groups. Results and Discussion: Vertebral levels detected by both techniques were compatible with 35 (46.6%) patients in Group P and 36 (60%) patients in Group NP (p = 0.165). The vertebral levels in Group P detected via ultrasound were determined at L2 in three (4%) patients, at L2/3 in three (4%) patients, at L3 intervals in three (4%) patients, and at the L3/4 interval in 31 (41.3%) patients. The vertebral levels of the patients in Group NP detected via ultrasound was at L2/3 in 2 (3.3%) patients, and at the L3/4 interval in 22 (36.7%) patients. For the risk of insertion from a risky injection site, the OR = 3.96–95 and GA = 0.82–19.05 in Group P were higher compared to Group NP (approximately 4 times higher). While Group P was significantly limited in the risk analysis, according to L3 (p = 0.087), the risk under this level was similar (p = 0.124). In this study, the verification of Tuffier’s line determined through palpation did not show the correct vertebral level in almost half of the patients in the lateral decubitus position, regardless of pregnancy and demographic data. Conclusion: We believe a possible spinal cord injury can be prevented by determining the needle insertion site via lumbar ultrasound in the pregnant patients. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 529-535